Knowledge, practice, and challenges in the use of stainless steel crowns and the Hall technique among Yemeni general dental practitioners: a cross-sectional study - Al-Rai, Sarah; Alyousefy, Mohanad; Al-Twaili, Zainab; Anqa, Eshraq; Amin, Mohammed; Al-bateit, Jameil; Al-Mogahed, Halah; Al-Batayneh, Ola B. (Frontiers in Oral Health, 2025)
ObjectivesStainless steel crowns (SSCs) and Hall technique (HT) are used to restore decayed primary molars. This study aimed to critically evaluate the practice, knowledge, and challenges faced by general dental practitioners (GDPs) in Yemen when restoring caries-affected primary molars using stainless steel crowns (SSCs) and the Hall technique (HT) in their routine clinical practice.MethodsA web-based cross-sectional survey was randomly distributed among GDPs registered with the Yemeni Dental Association using a Google Form (Google LLC, California, USA). The questionnaire comprised 21 questions organized into four sections: demographic information, SSC and HT practice, knowledge of SSC and HT, and challenges in SSC placement and HT use.ResultsA total of 501 participants were included in the final analysis, with (54.7%) were females and (45.3%) were males. The majority graduated from public universities (68.5%). SSCs were used in daily practice by 51.3%, primarily for multisurface caries (67.3%). A low percentage used HT (30.1%), with the main concern being insertion difficulty due to lack of preparation (43.5%). Age and residency place significantly influenced SSC usage (p = 0.01 and p < 0.001, respectively). Frequent SSCs use was higher among dentists >30 years and those with >10 years of experience (p < 0.001). No demographic factors were associated with HT use. However, females and younger practitioners <30 were more likely to report needing additional practical training (p = 0.023 and p = 0.04, respectively).ConclusionEnhancing GDPs' knowledge and skills in SSCs and HT through updated curricula and training could improve and enhance pediatric dental care.